Transcriptional networks in plant immunity. Issue 3 (26th January 2015) - Tsuda, Kenichi; Somssich, Imre E.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> 932 I. I. 932 II. II. 933 III. III. 934 IV. IV. 938 V. V. 941 943 References 943 </table-wrap> Summary Next to numerous abiotic stresses, plants are constantly exposed to a variety of pathogens within their environment. Thus, their ability to survive and prosper during the course of evolution was strongly dependent on adapting efficient strategies to perceive and to respond to such potential threats. It is therefore not surprising that modern plants have a highly sophisticated immune repertoire consisting of diverse signal perception and intracellular signaling pathways. This signaling network is intricate and deeply interconnected, probably reflecting the diverse lifestyles and infection strategies used by the multitude of invading phytopathogens. Moreover it allows signal communication between developmental and defense programs thereby ensuring that plant growth and fitness are not significantly retarded. How plants integrate and prioritize the incoming signals and how this information is transduced to enable appropriate immune responses is currently a major research area. An important finding has been that pathogen‐triggered cellular responses involve massive transcriptional reprogramming within the host. Additional key observations emerging from such studies are that transcription factors (TFs) are often sites of signal convergence and that signal‐regulated TFs act in concert with other context‐specific TFs and transcriptional co‐regulators to establish sensory transcription regulatory networks required for plant immunity.